Biocompatible oligo-oxazoline crosslinkers - Lopes, Mafalda (2021)
Associate Laboratory for Green Chemistry - LAQV which is financed by national funds from FCT/MCTES (UIDB/50006/2020 and UIDP/50006/2020).